APLIKASI PELAYANAN KAMAR ASRAMA PADA KANTOR LEMBAGA PENJAMINAN MUTU PENDIDIKAN: Application for dorm room service at the lembaga penjaminan mutu pendidikan (LPMP) office, West Papua Using codeigniter - Emil Masturah; Julius Panda Putra Naibaho; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2022)
The education house service (LPMP) west Papua Manpkwari (LPMP) manokwari is essentially a manual, such as the filling in of guest for housing registration in the LPMP manokwari dorm room. So it took a long time to do the process of checking out the empty rooms if any guests were to stay in the dorms. Thus the auther created an application for west Papua dorm room service using fremwork cedeigniter 3.0. From testing of the application using the black box method, it suggests that it is helpful to LPMP manokwari papua barat,especially the registration departemen in providing services to guests who have come to perform room registrasion.